Positive sleep outcomes associated with increased morning and daytime light exposure in elite team sport athletes - Stevenson, S.; Suppiah, H.; Ruddy, J.; Murphy, S.; Driller, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Light exposure techniques have been recommended to combat sleep issues caused by disruption to circadian regularity in the athletic population, although no studies have measured light exposure and sleep outcomes in an elite athlete setting. METHODS: A total of 17 professional male Australian Football athletes (age ± SD: 22 ± 3 years) wore a wrist actigraph to measure sleep parameters, and a wearable light sensor to measure melanopic equivalent daylight illuminance (mEDI, in lux) for 14 days. Participants completed three sleep questionnaires at the end of the data collection period and completed wellbeing surveys 6 times. The Sleep Regularity Index (SRI) for each player was also calculated from actigraphy data. Light exposure data were organised into three different timeframes; morning (wake time + 2 hours), daytime (end of morning to 6 pm), and evening (2 hours leading up to bedtime) for analysis. RESULTS: Higher morning light was associated with significantly (p < 0.01) greater total sleep time (r = 0.26). Higher daytime light exposure was associated with higher subjective sleep quality (r = 0.48, p < 0.05). Higher evening light exposure was associated with higher ASSQ global scores (r = 0.52, p < 0.01). There were no other significant correlations between light exposure and sleep or wellbeing measures (p > 0.05). CONCLUSION: Higher morning and daylight exposure levels were associated with various positive objective and subjective sleep measures in professional team sport athletes, supporting the need for education on optimising light exposure to improve circadian function, sleep, and health.